Sarcolemma wounding activates dynamin‐dependent endocytosis in striated muscle. (25th September 2020) - McDade, Joel R.; Naylor, Molly T.; Michele, Daniel E.
Abstract : Plasma membrane repair is an evolutionarily conserved mechanism by which cells can seal breaches in the plasma membrane. Mutations in several proteins with putative roles in sarcolemma integrity, membrane repair, and membrane transport result in several forms of muscle disease; however, the mechanisms that are activated and responsible for sarcolemma resealing are not well understood. Using the standard assays for membrane repair, which track the uptake of FM 1‐43 dye into adult skeletal muscle fibers following laser‐induced sarcolemma disruption, we show that labeling of resting fibers by FM1‐43 prior to membrane wounding and the induced FM1‐43 dye uptake after sarcolemma wounding occurs via dynamin‐dependent endocytosis. Dysferlin‐deficient muscle fibers show elevated dye uptake following wounding, which is the basis for the assertion that membrane repair is defective in this model. Our data show that dynamin inhibition mitigates the differences in FM1‐43 dye uptake between dysferlin‐null and wild‐type muscle fibers, suggesting that elevated wound‐induced FM1‐43 uptake in dysferlin‐deficient muscle may actually be due to enhanced dynamin‐dependent endocytosis following wounding, though dynamin inhibition had no effect on dysferlin trafficking after wounding. By monitoring calcium flux after membrane wounding, we show that reversal of calcium precedes the sustained, slower increase of dynamin‐dependent FM1‐43 uptake in WT fibers, and that dysferlin‐deficient muscle fibers have persistently increased calcium after wounding, consistent with its proposed role in resealing. These data highlight a previously unappreciated role for dynamin‐dependent endocytosis in wounded skeletal muscle fibers and identify overactive dynamin‐dependent endocytosis following sarcolemma wounding as a potential mechanism or consequence of dysferlin deficiency. Abstract : Dysferlin‐deficient muscle fibers show elevated uptake of the extracellular dye, FM1‐43, following wounding, which is the basis for the assertion that membrane repair is defective in this model. We show that the wound‐induced uptake of FM1‐43 occurs via dynamin‐dependent endocytosis. Further, dynamin inhibition mitigates the differences in wound‐induced FM1‐43 uptake between dysferlin‐null and wild‐type muscle fibers, suggesting that wounding may result in overactive dynamin‐dependent endocytosis in dysferlin‐deficient muscle fibers.